Research on factors influencing Chinese parents’ support for death education: a cross-sectional survey - Chen, Hejie; Xiao, Yuan; Huang, Xincheng; Fan, Siyuan; Wu, Haiwen; Li, Linxiao; Wu, Yibo (Frontiers in Public Health, 2024)
Objective] This study aims to explore the factors influencing Chinese parents' attitudes towards death education. Given the current lack of such education in China, this research is particularly significant. Death education is vital for shaping the values of young people and alleviating mental health issues, such as depression and suicidal tendencies. By identifying these influencing factors, this study seeks to provide guidance for policymakers and educators in promoting the development and widespread adoption of death education.[Methods] To do so, a national cross-sectional quota sample of 12,435 Chinese parents was used.Borrowing from social-ecological theory, the researchers carried out multiple stepwise regression analyses to examine the individual, family, and social-level factors that shape the supportive attitudes of Chinese parents towards death education.[Result] The findings revealed that at the individual level, parent (β=0.04, p<0.001), education level (β=0.07, p<0.001), and religious belief (β=-0.02, p<0.05) were significant predictors of Chinese parents' support for death education. Meanwhile, at the family and social level, average monthly household income (β=0.07, p<0.001), family health (β=0.03, p<0.05), family communication (β=0.02, p<0.05), social support (β=0.15, p<0.001), neighborhood relations (β=0.11, p<0.001), and social network size (β=0.05, p<0.001) were significant predictors of Chinese parents' supportive attitudes towards death education.[Conclusion] Based on these findings, it is suggested that the relevant development, planning, publicity, and public welfare groups and government departments should promote death education, provide more social support, and encourage neighborhood harmony. As higher education and average monthly household income were found to significantly impact the support, the government should improve access to higher education and actively work to increase residents' income to facilitate the development of death education.